Relevance of Social Security Allowance in Nepal - Malakar, Indra Mali (Innovative Research Journal, 2022)
This study aims at assessing the relevance of social security allowance in Nepal among the beneficiaries of Kirtipur Municipality, Kathmandu district. With purposive selection of Kirtipur Municipality, a community based cross sectional study was carried out among old age allowance beneficiaries of Kirtipur Municipality. Most of the target people (86.1% male and 85.6% female) of social security allowance have been primarily using allowance money for basic personal needs for buying food/clothes/vegetables and though the government’s initiatives have had the direct bearing on the reduction of the household economic poverty and vulnerability of the beneficiaries, it seems insufficient enough to maintain the target people’s life as majority of them (80.4%) reported the inadequacy of the allowance distributed. This was evidenced by chi-square test also. The study revealed that there is needed to make the institutional efforts within the legal framework to make members of the families responsible for the support of senior citizens in their ripe old age. The government needs to design and implement livelihoods programs for physically capable senior citizens living below poverty line which would also use their skill and knowledge and contribute to reduce household poverty.